Perlindungan Hukum Barang Milik Daerah (BMD) Yakni Tanah dan Bangunan dalam Perjanjian Pinjam Pakai : Analisis terhadap Kasus Komite Olahraga Nasional Indonesia Kabupaten Sumenep: Indonesia - Nany Amellia Nurfadiah; Ansori Ansori (Referendum : Jurnal Hukum Perdata dan Pidana, 2024)
This research aims to analyze the legal aspects contained in loan-to-use agreements related to the use of regional property, especially land and buildings. In addition, this research aims to evaluate the implementation of Minister of Home Affairs Regulation (Permendagri) number 19 of 2016 concerning Guidelines for Management of Regional Property which has undergone changes through Home Affairs Government Regulation number 7 of 2024 concerning Amendments to Permendagri number 19 of 2016 concerning Property Management Regionally Owned. Furthermore, this research also aims to identify the terms and conditions governing the use of regional property in the Borrow-Use Agreement for regional assets in the form of land and buildings proposed by the Indonesian National Sports Committee, Sumenep Regency. The method used in this research is a qualitative research method with a focus on empirical legal research. The research results indicate that the Indonesian National Sports Committee is not included in the legal subjects regulated by the Borrow-Use Agreement for Regional Property. This is due to the character of KONI which is a non-governmental organization. In practice, KONI cannot implement loan-to-use agreements on regional assets; However, KONI still has the opportunity to enter into an agreement to utilize other regional assets.